Videogrammetry for human movement analysis - Remondino, F. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
The paper briefly recalls the concepts of photogrammetric analysis of video sequences for the study of human movements. The concepts of real-time processing, calibration and orientation and multi-image correspondences are outlines. Standard multi-camera systems as well as monocular approaches are reported and discussed.